Adaptive H∞ fault-tolerant control for a class of uncertain switched nonlinear systems with multiple state time delays. Issue 8 (11th June 2018) - Wu, Li-Bing; He, Xi-Qin; Zhang, Da-Qing; Jia, Hong-Wei
ABSTRACT: This paper studies the adaptiveH ∞ fault-tolerant control problem for a class of uncertain switched nonlinear time-delayed systems with mismatching parameter uncertainties, nonlinear functions, external disturbances and actuator failures. By using the estimations of the unknown upper bounds of uncertain parameters, the novel adaptive laws based on state-dependent switching strategy are constructed, and then the effects of multiple state time delays and actuator failures can be eliminated. Moreover, by using the robustH ∞ technique and multiple Lyapunov functions method, the designed controller can guarantee the asymptotic stability and the desiredH ∞ performances of the switched closed-loop systems in the presence of parameter uncertainties and time-delayed perturbation simultaneously. Finally, simulation results are provided to show the efficiency of the proposed robust adaptive control scheme.